1987
DOI: 10.1126/science.3296194
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Map of the Escherichia coli K12 Genome

Abstract: A physical map of a genome is the structure of its DNA. Construction of such a map is a first step in the complete characterization of that DNA. The restriction endonuclease Not I cuts the genome of Escherichia coli K12 into 22 DNA fragments ranging from 20 kilobases (20,000 base pairs) to 1000 kilobases. These can be separated by pulsed field gel electrophoresis. The order of the fragments in the genome was determined from available E. coli genetic information and analysis of partial digest patterns. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
229
2
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(240 citation statements)
references
References 56 publications
7
229
2
2
Order By: Relevance
“…Therefore, in order to determine the size of un-sheared vesicular DNA, we lysed EVs directly in agarose plugs and resolved EV DNA by PFGE [26]. Resolution of high molecular weight DNA, which was possible with this method, revealed that L-EVs contain DNA fragments up to 2 Mega base pair (Mbp) (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to determine the size of un-sheared vesicular DNA, we lysed EVs directly in agarose plugs and resolved EV DNA by PFGE [26]. Resolution of high molecular weight DNA, which was possible with this method, revealed that L-EVs contain DNA fragments up to 2 Mega base pair (Mbp) (Figure 1(a)).…”
Section: Resultsmentioning
confidence: 99%
“…EVs (or indicated number of donor cells) were resuspended in PBS, mixed with the equal volume of 1% low melting agarose and embedded into Plug Mold (BIO-RAD) as previously described [26]. Agarose plugs were then incubated in lysis buffer containing 1% SDS and 1 mg/ml proteinase K at 37°C for 24, 48 or 72 h and washed with TE buffer, before the plugs were treated with 1 mg/ml RNase A at 37°C for 1 h. Pulse field gel electrophoresis (PFGE) was carried out in 1% agarose gel with 0.5× TBE buffer using CHEF Mapper XA System (BIO-RAD).…”
Section: Methodsmentioning
confidence: 99%
“…[8,11,12] such techniques often produce complex patterns that are difficult to interpret. Pulsed-field gel electrophoresis (PFGE) allows the analysis of large fragments produced by the digestion of DNA with rare cutter enzymes [13]. This method has been used to study the epidemiology and molecular biology of a number of bacterial species, to obtain physical maps of bacterial genomes and to determine the map locations of markers not previously mapped and/or new mutations [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE) allows the analysis of large fragments produced by the digestion of DNA with rare cutter enzymes [13]. This method has been used to study the epidemiology and molecular biology of a number of bacterial species, to obtain physical maps of bacterial genomes and to determine the map locations of markers not previously mapped and/or new mutations [13][14][15][16]. It has proved to be highly discriminatory and has enabled the resolution of isolates indistinguishable by serological classification methods, antimicrobial susceptibility and ribotype.…”
Section: Introductionmentioning
confidence: 99%
“…In general, refinement of a genetic map requires detection of increasingly rarer events, which in turn requires analysis of a greater number of meiotic events (i.e., the progeny of matings). In mammals, such as man, even the best 20 mapped regions of the genome only achieve a resolution of approximately 1 Mb (Fulton et al, 1989;Gardiner and Patterson, 1989;Gemmill et al, 1987;Michiels et al, 1987;Pohl et al, 1988;Poustka et al, 1987;Shaw, 1986;Smith et al, 1987aSmith et al, , 1987bVentra and Weiss, 1989;Wallace et al, 1989). …”
mentioning
confidence: 99%